Teaching English in Today’s World - S Mohanraj (International Conference on Education and Language (ICEL), 2013)
The teaching of English as a second/foreign language in the world at large has taken a new turn in the context of globalization.  In accordance with the changing needs, materials for use in language teaching and strategies adopted have also seen substantial change.The present paper discusses the principal reasons for English acquiring a global status.  With such change coming over, there has been a proliferation of Englishes and every country teaching this language has the difficult decision to make a choice of the variety.  Besides the variety, the academic interests are also at stake.Another change that concerns the academics in the field of English language teaching pertains to harness English across curriculum. This aspect of language teaching needs to focus on specialized vocabulary.  Facilities to identify the words required for special branches of study and their uses are available through corpus analysis. How do we capture such diverse needs and harness the facilities available in our daily teaching forms the theme of this presentation.